Penyuluhan pengetahuan tentang pencegahan anemia pada remaja putri - Rismawati Rismawati; Andi Fatima; Nursyam Nursyam (JOURNAL of Public Health Concerns, 2025)
Background: Adolescence is when physically and psychologically they are still growing and developing. Physical activity and nutritional intake are supporting factors in creating a healthy lifestyle balance. With the lack of attention to the balance of a healthy lifestyle in adolescents, adolescents are vulnerable to having health problems. One of them is the occurrence of anemia in adolescents, especially adolescent girls. The lack of red blood cells in the body causes symptoms of anemia such as fatigue, tiredness, and decreased physical activity. Globally, the prevalence of anemia in women aged 15 years and over is 28%. In Indonesia, the prevalence rate of anemia is around 40.1% and this figure is quite high. Purpose: To increase the knowledge of adolescent girls about the causes of anemia. Method: The counseling activity was carried out on Monday, July 2, 2024 at 09.00 WITA at SMA Negeri 18 Makassar. The activity was attended by all students of SMAN 18, the principal, and teaching staff. The counseling was carried out using the lecture method, then the delivery of material about the causes and symptoms of anemia in adolescents. Results: Participants gained knowledge about anemia and positive responses were also shown during the discussion and Q&A sessions related to the causal factors that cause anemia and its symptoms. Food or intake factors are among the most important factors in preventing anemia, in addition to nutritional balance, healthy lifestyles and regular physical activity. Conclusion: Counseling about anemia provided a significant increase in knowledge for adolescents related to understanding the symptoms and prevention of anemia. Positive responses and proactive attitudes from participants in this activity showed an increase in knowledge about the importance of a healthy lifestyle in preventing anemia. Keywords: Adolescent girls; Anemia; Symptoms of anemia Pendahuluan: Usia remaja adalah dimana secara fisik dan psikologis masih dalam masa tumbuh kembang. Aktifitas fisik dan asupan gizi merupakan faktor pendukung dalam menciptakan keseimbangan pola hidup sehat. Dengan kurangnya perhatian terhadap keseimbangan pola hidup sehat pada remaja sehingga rentan bagi remaja untuk mendapati masalah dengan kesehatannya. Salah satunya adalah kejadian anemia pada remaja, khususnya remaja putri. Kurangnya sel darah merah dalam tubuh menimbulkan dampak gejala anemia seperti mudah lelah, letih, dan aktifitas fisik menjadi menurun. Secara global prevalensi kejadian anemia pada perempuan usia 15 tahun ke atas sebesar 28%. Di Indonesia tingkat prevalensi anemia sekitar 40.1% dan angka tersebut tergolong tinggi. Tujuan: Untuk meningkatkan pengetahuan remaja putri tentang penyebab kejadian anemia. Metode: Kegiatan penyuluhan dilaksanakan pada hari Senin, tanggal 02 Juli 2024  pada pukul 09.00 wita bertempat di  SMA Negri 18 Makassar. Kegiatan dihadiri oleh seluruh siswa/siswi SMAN 18, kepala sekolah, dan para staf pengajar. Penyuluhan dilakukan dengan menggunakan metode ceramah selanjutnya penyampaian materi tentang penyebab dan gejala anemia pada remaja putri. Hasil: Peserta mendapatkan pengetahuan tentang anemia dan respon positif juga ditunjukkan ketika sesi diskusi dan tanya jawab terkait faktor-faktor penyebab yang menjadikan timbulnya anemia dan gejalanya. Faktor makanan atau asupan adalah termasuk faktor terpenting dalam mencegah kejadian anemia, selain keseimbangan gizi, pola hidup sehat dan aktifitas fisik yang teratur. Simpulan: Penyuluhan tentang anemia memberikan peningkatan pengetahuan yang signifikan terhadap remaja putri terkait pemahaman gejala dan pencegahan kejadian anemia. Respon positif dan sikap proaktif dari para peserta dalam kegiatan ini menunjukkan adanya peningkatan pengetahuan tentang pentingnya pola hidup sehat dalam mencegah kejadian anemia.